Effects of Statin Therapy and Dose on Cardiovascular and Limb Outcomes in Peripheral Arterial Disease: A Systematic Review and Meta-analysis - Sofat, Samick; Chen, Xiaoyu; Chowdhury, Mohammed M.; Coughlin, Patrick A. (European journal of vascular and endovascular surgery, 2021)
Statin therapy is indicated in patients with peripheral arterial disease (PAD). National Institute for Health and Care Excellence guidelines suggest the use of “high intensity” statins, although evidence with PAD specific data are lacking. The effect of statin therapy and dose on outcomes in PAD is investigated. Studies measuring statin use in PAD patients and outcomes were identified based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. The EMBASE and MEDLINE databases were interrogated from January 1957 until February 2020. Twenty-two observational cohort studies and two randomised control trials were included (n = 268 611). Pooled estimates of dichotomous outcome data were calculated using the odds/hazard ratios (OR/HR) and 95% confidence interval (CI). Meta-analysis was conducted using the inverse variance or Mantel–Haenszel method. Outcomes included all cause mortality (ACM), cardiovascular mortality (CVM), major adverse cardiac events (MACE), and amputation. Subgroup analysis was performed on studies comparing patients taking high dose vs. combined low and moderate doses of statins. The GRADE criteria assessed the quality of evidence for outcomes. Statin therapy (vs. no statins) was significantly protective for ACM: OR 0.68 (95% CI 0.60 – 0.76) (number needed to treat [NNT] = 48), HR 0.74 (95% CI 0.70 – 0.78) (NNT = 10 – 91); MACE: OR 0.84 (95% CI 0.78 – 0.92) (NNT = 53), HR 0.78 (95% CI 0.65 – 0.93) (NNT = 167); and amputations: OR 0.59 (95% CI 0.33 – 1.07) (NNT = 333), HR 0.74 (95% CI 0.62 – 0.89) (NNT = 50). High doses of statins (vs. combined low and moderate doses) were significantly better protective against ACM OR 0.69 (95% CI 0.43 – 1.09) (NNT = 17), HR 0.74 (95% CI 0.62 – 0.89) (NNT = 16 – 200) but work less significantly for MACE OR 0.77 (95% CI 0.49 – 1.21) (NNT = 25). Amputations were less frequent in patients on high doses HR 0.78 (95% CI 0.69 – 0.90) (NNT = 53 – 1 000). Higher dosing of statins confers a significant improvement in patient outcomes, especially ACM and amputations, although the quality of the evidence was variable. Such findings require confirmation in larger, PAD specific trials.